2008
DOI: 10.1007/s11517-008-0392-1
|View full text |Cite
|
Sign up to set email alerts
|

Approximate entropy and auto mutual information analysis of the electroencephalogram in Alzheimer’s disease patients

Abstract: We analysed the electroencephalogram (EEG) from Alzheimer's disease (AD) patients with two non-linear methods: Approximate Entropy (ApEn) and Auto Mutual Information (AMI). ApEn quantifies regularity in data, while AMI detects linear and non-linear dependencies in time series. EEGs from 11 AD patients and 11 age-matched controls were analysed. ApEn was significantly lower in AD patients at electrodes O1, O2, P3 and P4 (p < 0.01). The EEG AMI decreased more slowly with time delays in patients than in controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
86
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 48 publications
15
86
0
8
Order By: Relevance
“…Our results support the idea that the AMIFRD, which is correlated with signal entropy (Abásolo et al 2008, Paluš 1996, is an irregularity estimator instead of a complexity measure, as some authors have previously suggested (Jeong et al 2001, Na et al 2002, Palacios et al 2007. From a strict point of view, a quantitative measure of complexity should vanish for both completely ordered and completely random signals like white noise, which is very unpredictable but not structurally complex (Costa et al 2005).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Our results support the idea that the AMIFRD, which is correlated with signal entropy (Abásolo et al 2008, Paluš 1996, is an irregularity estimator instead of a complexity measure, as some authors have previously suggested (Jeong et al 2001, Na et al 2002, Palacios et al 2007. From a strict point of view, a quantitative measure of complexity should vanish for both completely ordered and completely random signals like white noise, which is very unpredictable but not structurally complex (Costa et al 2005).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the use of the AMIFRD as a characterising metric in the analysis of experimental recordings has some advantages. Firstly, it can be applied to short time series in comparison to other non-linear classical analysis methods, such as the correlation dimension (Abásolo et al 2008, Gómez et al 2007, Jeong et al 2001. Secondly, the only input parameter for the AMIF is the number of histogram partitions (Jeong et al 2001, Na et al 2002.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations